Vol 2 No 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: PERANAN KOPERASI DALAM MENINGKATKAN EKONOMI KERAKYATAN - nidhom, Misbahun (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
Cooperatives as business entities that are owned and utilized by members, are confirmed in Law number 25 of 1992. The boundaries of cooperatives in this law have a stricter and clearer meaning than the old boundaries, in Law no. 12 of 1967, which allowed the creation of dual thinking about cooperatives. Law number 25 of 1992 accommodates changes at the instrumental level, such as the regulation of "Managers" or managers in managing cooperatives. Cooperatives, like other business entities, have freedom of movement in carrying out business as long as they do not violate existing statutory provisions and normative ideology. Business is a rational process that ultimately leads to the creation of profits, the accumulated profits are used to serve members' needs.